Cervicofacial subcutaneous emphysema associated with dental laser treatment. (December 2013) - Mitsunaga, S; Iwai, T; Kitajima, H; Yajima, Y; Ohya, T; Hirota, M; Mitsudo, K; Aoki, N; Yamashita, Y; Omura, S; Tohnai, I
Abstract Cervicofacial subcutaneous emphysema is a rare complication of dental procedures. Although most cases of emphysema occur incidentally with the use of a high‐speed air turbine handpiece, there have been some reports over the past decade of cases caused by dental laser treatment. Emphysema as a complication caused by the air cooling spray of a dental laser is not well known, even though dental lasers utilize compressed air just as air turbines and syringes do. In this study, we comprehensively reviewed cases of emphysema attributed to dental laser treatment that appeared in the literature between January 2001 and September 2012, and we included three such cases referred to us. Among 13 cases identified in total, nine had cervicofacial subcutaneous and mediastinal emphysema. Compared with past reviews, the incidence of mediastinal emphysema caused by dental laser treatment was higher than emphysema caused by dental procedure without dental laser use. Eight patients underwent CO2 laser treatment and two underwent Er:YAG laser treatment. Nine patients had emphysema following laser irradiation for soft tissue incision. Dentists and oral surgeons should be cognizant of the potential risk for iatrogenic emphysema caused by the air cooling spray during dental laser treatment and ensure proper usage of lasers.